Evolutionary Adaptations of Deep-Sea Creatures: Climate Change and Captive Fish Migration - Aslam, Mehak; Hassan, Hammad; Ahmed, Zunnorain; Memon, Shakeel Ahmed; Tahir, Waniza; Fatima Ishaq,; Umber Rauf,; Qamar, Hira; Bashir, Malka Saba; Sabir, Anum (Indus Journal of Bioscience Research, 2025)
The deep sea, encompassing more than 60% of Earth's surface, constitutes one of the planet's harshest and least investigated ecosystems, inhabited by species with remarkable adaptations to high pressure, constant darkness, and limited supplies. These adaptations facilitate life in extreme environments but render deep-sea organisms particularly susceptible to the persistent effects of climate change and anthropogenic activities, such as deep-sea mining and bottom trawling. This review examines the evolutionary adaptations of deep-sea species and emphasizes their physiological, morphological, and behavioral mechanisms. It analyses the impact of climate change-related stressors, such as increasing ocean temperatures, acidification, and deoxygenation, on their survival and dispersal. Furthermore, it examines deep-sea fish's migration patterns and captive habits, emphasizing their ecological importance and conservation challenges. This study synthesizes findings from several studies to identify significant knowledge gaps, particularly concerning the long-term impacts of multiple stressors and the contribution of the deep sea to the global carbon cycle. Using an interdisciplinary approach, it proposes actionable recommendations for future research, including studies on physiological resilience and applying genomic technologies to explore adaptation mechanisms. These findings guide conservation initiatives, including establishing marine protected zones and enforcing international restrictions on deep-sea resource extraction. This study underscores the significance of conserving deep-sea biodiversity to sustain ecosystem integrity and global climate equilibrium. It establishes a basis for enhancing research and policy in this vital domain.